2006
DOI: 10.1007/s10517-006-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural polysaccharide carrageenan inhibits toxic effect of gram-negative bacterial endotoxins

Abstract: The protective effect of polysaccharide carrageenan on the damaging effect of endotoxins of gram-negative bacteria was studied in vivo and in vitro. Carrageenan increased mouse resistance to the toxic effect of LPS. The degree of protection depended on polysaccharide concentration and administration time and route. Pretreatment of donor platelets with carrageenan reduced their aggregation activity caused by cooperative effect of LPS and ADP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…The degree of protection depended on carrageenan type. Pretreatment with kappa-carrageenans significantly prolonged the survival of mice after an E. coli and Y. pseudotuberculosis LPS-challenge (Ermak et al 2006). The mechanism of host Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The degree of protection depended on carrageenan type. Pretreatment with kappa-carrageenans significantly prolonged the survival of mice after an E. coli and Y. pseudotuberculosis LPS-challenge (Ermak et al 2006). The mechanism of host Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The administration of iota-carrageenan also has been reported to increase the innate immune response of the orange spotted grouper Epinephelus coioides and its resistance against V. alginolyticus via injection (Cheng et al 2007). We previously showed (Ermak et al 2006) that carrageenans reduced the toxic effect of Eschericia coli and Yersinia pseudotuberculosis LPS. The degree of protection depended on the structure of carrageenans, polysaccharide concentration and administration time.…”
Section: Introductionmentioning
confidence: 98%
“…Others such as hydroxysafflor yellow A and ferulic acid are also reported [12]. It has been found that some of them have specific effects against platelet aggregation [13]. According to the preparation of extracts (combination) and the retention mechanism on reverse phase chromatographic column, these 48 constituents may in turn correspond to the compounds of polysaccharide, saponins, and flavonoids.…”
Section: Classes Of the 48 Constituentsmentioning
confidence: 99%
“…Many of the marine macro algae produce a variety of secondary metabolites, such as polyphenols, terpenes, sterols, lectins, inhibitors of proteinases, fatty acids, enzymes, and polysaccharides (Smit 2004;Barabanova et al 2005;Ermak et al 2006) which act as potential bioactive compounds of interest for pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%